2018
DOI: 10.1155/2018/8031253
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated Pleomorphic Sarcoma of Liver: Case Report and Review of the Literature

Abstract: Undifferentiated pleomorphic sarcoma (UPS), previously known as malignant fibrous histiocytoma (MFH), is rarely reported in the liver as a primary site. We report a case of a previously healthy 56-year-old male, who presented with abdominal pain and jaundice. The patient was originally diagnosed with cholecystitis, treated with cholecystectomy, which was complicated by abdominal abscess. One week following discharge, the patient was readmitted with fever, chills, and leukocytosis. Computed tomography (CT) guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Symptoms of primary hepatic UPS are generally nonspecific. Patients frequently complain of abdominal pain, weight loss, anorexia, fever, jaundice, malaise, and a palpable abdominal mass [ 4 , 5 ]. Diagnostic tools including radiological imaging and laboratory studies are insufficient to make the diagnosis of UPS.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of primary hepatic UPS are generally nonspecific. Patients frequently complain of abdominal pain, weight loss, anorexia, fever, jaundice, malaise, and a palpable abdominal mass [ 4 , 5 ]. Diagnostic tools including radiological imaging and laboratory studies are insufficient to make the diagnosis of UPS.…”
Section: Discussionmentioning
confidence: 99%
“…The co-existence of a low attenuation solid mass and a cystic component with mural calcification may be an important hint to consider splenic UPS. Prior literature showed that UPS is FDG avid on FDG-PET/CT, [33–35] which appears to apply to splenic UPS as well. [27] CT findings as mentioned above may be useful to avoid delaying radical surgery early in the splenic UPS disease course.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, the World Health Organization (WHO) declassified MFH as a formal diagnostic entity and renamed it as UPS, not otherwise specified [2]. UPS represents a final common pathway in tumors that undergooes progression towards dedifferentiation [3]. We report a man with UPS presenting as an exophytic pedunculated tumor of the left scapula.…”
Section: Introductionmentioning
confidence: 99%